Association of the hypoxia-inducible factor-1α (HIF-1α) gene polymorphisms with prognosis in ovarian clear cell carcinoma - Hiroyuki Suzuki; Mitsutake Yano; Mariko Miyazawa; Masaki Miyazawa; Naoki Ogane; Kosei Hasegawa; Hitoshi Tsuda; Masayuki Yoshida; Ryugo Okagaki; Osamu Ishihara; Masanori Yasuda (BMC, 2019)
Abstract Background Ovarian clear cell carcinoma (OCCC) is the second most common ovarian cancer after serous carcinoma in Japan. OCCC has a more unfavorable clinical outcome due to a poor response to platinum-based chemotherapy, compared with serous carcinoma. Hypoxia inducible factor-1α (HIF-1α) is a key regulator of cellular response to hypoxia and plays an important role in tumor growth, and HIF-1α gene single-nucleotide polymorphisms (SNPs) adversely affect the outcome in some cancers. Herein, we investigated the association of the HIF-1α gene SPNs with clinical outcome in OCCCs. Eighty-nine patients with OCCC were recruited in whom pathological diagnosis was confirmed with surgically resected specimen. Results The SNPs of C1772T and G1790A in the HIF-1α gene occurred in 23.6 and 3.3% of the patients, respectively. In the univariate analysis, overall survival was associated with stage and surgical residual tumor but not with the SNPs C1772T, G1790A, C1772T and/or G1790A. In the multivariate survival analysis, a significant association was observed between outcome and FIGO stage and/or surgical residual tumor; however, no association was obtained between HIF-1α gene SNPs and these factors. Conclusion In conclusion, unlike the other cancers in which HIF-1α gene SNPs were demonstrated to be associated with the outcome, OCCC prognosis may not be affected by HIF-1α gene SNPs. Further studies need to be performed to clarify the association of HIF-1α expression with the unfavorable prognosis in OCCCs, in terms of transcriptional/translational activity, nuclear translocation of the protein, and protein degradation.